Morphometric evaluation of Upper Ramganga basin using geospatial techniques - GAUTAM, UPMA; TIWARI, VIVEK; KUMAR, JITENDRA; KUMAR, MUKESH (Journal of Soil and Water Conservation, 2022)
Watershed is an important ecosystem in which all natural resources i.e. soil, water and vegetation coexists. The interrelationship between terrain, geomorphology, land use and morphometric parameters are important to understand hydrological behaviour at the basin level. In the present paper, an attempt has been made to study the morphometric analysis of a watershed of upper ramganga basin in uttarakhand India using GIS. For the study, ASTER DEM (Digital Elevation Model) of 30 m spatial resolution and IRS-1C LISS 3 files and ArcSWAT (Soil and Water Assessment Tool) were used in delineate basin boundary and evaluate of linear, areal, and relief aspect of morphometric parameters. The stream order of selected basin range from first to fourth. The range value of drainage density and bifurcation ratio varies from 0.009 to 0.69 km-1 and 1.1 to 2.4, respectively. The mean elongation ratio of basin was found to be 0.65 indicating that the basin is elongated in shape with gentle slope and long flow path. The hypsometric analysis of upper ramganga basin indicated that the basin was in equilibrium stage. The findings of study will be most useful in modelling of watershed management and developing functional relationship between geomorphologic parameters and hydrological response.